2013
DOI: 10.1007/s00018-013-1258-8
|View full text |Cite
|
Sign up to set email alerts
|

Vaspin inhibits kallikrein 7 by serpin mechanism

Abstract: not related to vaspin-mediated changes in insulin sensitivity as determined by euglycemic-hyperinsulinemic clamp studies. Improved glucose metabolism could be mediated by increased insulin plasma concentrations 150 min after a glucose challenge in db/db mice, supporting the hypothesis that vaspin may inhibit insulin degradation by hK7 in the circulation. In conclusion, we demonstrate the inhibitory serpin nature and the first protease target of the adipose tissue-derived serpin vaspin, and our findings suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
150
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 135 publications
(160 citation statements)
references
References 57 publications
6
150
1
3
Order By: Relevance
“…Insulin-resistant mouse models exhibit improved glucose tolerance after intraperitoneal vaspin application (3,4), and transgenic mice overexpressing vaspin are protected from diet-induced obesity and comorbidities, such as glucose intolerance, insulin resistance, and adipose tissue inflammation (5). We found that intraperitoneal and central administration of vaspin leads to reduced food intake and blood glucose in mice (6).…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…Insulin-resistant mouse models exhibit improved glucose tolerance after intraperitoneal vaspin application (3,4), and transgenic mice overexpressing vaspin are protected from diet-induced obesity and comorbidities, such as glucose intolerance, insulin resistance, and adipose tissue inflammation (5). We found that intraperitoneal and central administration of vaspin leads to reduced food intake and blood glucose in mice (6).…”
mentioning
confidence: 82%
“…KLK7 also cleaves recombinant vaspin after Tyr 30 , resulting in loss of the N-terminal His tag and vaspin residues Lys 22 -Tyr 30 (4). We therefore used the R302E mutant, which due to the negative charge at the exosite for KLK7 is not cleaved within the RCL, but only at the N terminus.…”
Section: Role Of N-terminal Basic Residues In Heparinmentioning
confidence: 99%
See 2 more Smart Citations
“…12 This beneficial effect has been related by Heiker et al to inhibition of kallikrein 7 by vaspin, which is a member of serine protease inhibitor family. 13 There is possibility that vaspin has compensatory effect in insulin resistance. Besides, there is a potential correlation of vaspin with the chronic inflammation in the diabetic patients.…”
Section: Introductionmentioning
confidence: 99%